Identification of coral disease within the high-latitude reef, Lord Howe Island Marine Park - Moriarty, Tess; Ainsworth, Tracy D.; Leggat, William (Frontiers in Ecology and Evolution, 2023)
Coral disease prevalence has significantly increased under a changing climate, impacting coral community structure and functionality. The impacts and ecology of coral diseases are unclear in most high-latitude reefs (coral reefs above 28 ° north and below 28 ° south.). High-latitude locations are vulnerable to climate change; therefore, identifying diseases and developing region-specific baselines are important for local management. We report the first coral disease findings at the UNESCO World Heritage listed Lord Howe Island Marine Park (31.5°S, 159°E), the southernmost coral reef system. This study assessed coral disease prevalence during November 2018, March 2019 and October 2019. Surveys from three lagoonal reefs identified four coral diseases: white syndrome, skeletal eroding band, growth anomalies and endolithic hypermycosis impacting six coral taxa (Acropora, Isopora, Montipora, Pocillopora, Porites and Seriatopora). Overall, disease prevalence was 5 ± 1 % and significantly differed between time and site. Disease prevalence was highest in November 2018 (10 ± 1 %) and significantly lower during March 2019 (5 ± 1 %), coinciding with a bleaching event. White syndrome was the most prevalent disease (4 ± 1 %) with 83 colonies of six taxa affected, predominately Isopora. Acroporids recorded the highest disease susceptibility, with three of the four diseases observed. Documenting baseline coral disease prevalence and monitoring throughout a bleaching event assists our understanding of disease ecology dynamics under current climate change impacts at high-latitude reefs.